Estimation and Distribution of Nitrate Contamination in Groundwater of Wah Town, its Causes and Management - Khan, Mohammad Saleem; Ahmad, Sajid Rashid; Rahman, Zaka ur; Ishaque, Muhammad (Pakistan Journal of Nutrition, 2012)
The increase in population at a very fast pace during the past few decades and related anthropogenic activities have created a number of environmental problems such as air pollution, water contamination and effects of solid waste dumping on environment. To accommodate and provide residence facilities to growing population number of residential colonies were developed in private sector in the surrounding of Wah town nearby Dhamrah Kas Nullah. Due to short of necessary facilities for on line disposal through treatment plants, the local citizen disposed off their sewage waste into low lying areas which have been converted into a number of sewage ponds and small lakes. These sewage ponds are one of the major sources of water contamination from where nitrate contaminants migrated into unconfined aquifer. To assess the nitrate concentration water sampling was carried out from 27 dugwells and 3 tubewells which are being used by local inhabitants for drinking water from shallow aquifer located at the depth of 45 to 85 feet in the study area. The results indicate that 26% wells related to the shallow aquifer are contaminated and have crossed the WHO recommended guidelines for nitrate level. Two zones with high nitrate contamination have been identified within the study area. Few samples collected from deep aquifer for comparison indicates that it is still safe from nitrate contamination. Suggestions have also been made to improve the situation.